Characterization of Eco-Friendly Straw Based on Chitosan from Pupae Exuviae of Black Soldier Fly (Hermetia illucens) - Rico Sulaeman; Raden Roro Zakiah Diva Wisnu Putri; Regita Damayanti; Fathan Fauzan; Muhammad Ribhan Hadiyan; Yani Maharani (Research and Development Center for Food, Nutrition and Public Health (P4GKM) LPPM UNS, 2024)
Utilizing materials with high natural degradation capabilities is viable for managing a sustainable environment. Chitosan derived from the exuvia of black soldier flies-BFS (Hermetia illucens) offers a potential alternative to chitosan sourced from crustaceans and food plants. It can be used to create straws and other chitosan-based products. The research aimed to analyze the characterization of chitosan from BSF exuvia as an environmentally friendly raw straw material. This study began by collecting BSF pupae exuviae, which was cleaned and dried for chitosan extraction. The test was carried out using various levels of chitosan, i.e., 0%, 0.5%, 1%, 1.5%, and 2%, with observation parameters on tensile strength and elongation, biodegradability, water absorption, and contact angle. The research was conducted with 5 repetitions per sample at each chitosan concentration level. The results showed that higher concentrations of chitosan led to increased tensile strength, ranging from 1.38 to 3.65 N mm-². The contact angle and hydrophobicity values varied between 69.87° and 103.66°, while the elongation at break values ranged from 4.5 to 285%. The 4 formulas on the biodegradability test showed no noticeable difference according to statistical analysis of variance (ANOVA test). Based on the formulation tested, a chitosan concentration of 2% (P4) is the best formulation as an ingredient in making eco-friendly straw.